A pre-solution mixing precursor method for improving the crystallization quality of perovskite films and electroluminescence performance of perovskite light-emitting diodes. Issue 43 (28th October 2019) - Xia, Pengfei; Lu, Yao; Yu, Hongtao; Li, Yongzhe; Zhu, Wenjing; Xu, Xin; Zhang, Wenzhu; Qian, Jie; Shen, Wei; Liu, Lihui; Deng, Lingling; Chen, Shufen
Abstract : A novel pre-solution mixing method is used to reduce ultrathin perovskite nanosheets in perovskite films and significantly enhance electroluminescence performances of PeLEDs. Abstract : Quasi-two-dimensional (Q-2D) perovskites are one kind of efficient luminescent material with fast energy transfer and radiative decay of excitons due to the energy cascade formed by the mixed perovskite phase. However, the existence of monolayer or bilayer nanosheets in the Q-2D perovskite film results in poor charge transport, high trap density and rough film surface because of the high ratio of ligands, which leads to poor performance of Q-2D perovskite light-emitting diodes (PeLEDs). Herein, we proposed a new strategy of a pre-solution mixing (PSM) precursor to inhibit the formation of ultrathin perovskite nanosheets, which significantly enhanced the charge carrier mobility, reduced the concentration of defects and improved the film morphology. The PeLEDs based on the PSM precursor achieved the maximum luminescence of 7832.1 cd m −2 (∼218% enhancement) and the peak current efficiency of 6.0 cd A −1 (∼131% enhancement). By introducing mixed cations in the PeLED, the maximum brightness of 14 211.0 cd m −2 and current efficiency of 14.6 cd A −1 were realized, demonstrating the generality of our PSM method for the preparation of high performance PeLEDs.